Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V SD - Nurwani Nurwani (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The purpose of this study was to improve the learning outcomes of SDI Maruala Students, Tanete Riaja District, Barru Regency through the Application of Scientific Approach Learning through the Teams Game Tournament (TGT) Method. The research method used is this type of research is classroom action research (CAR), with implementation stages including: (1) planning, (2) implementation, (3) observation and evaluation, (4) reflection. The conclusion in this research is that the application of a scientific approach to learning through the Teams Game Tournament (TGT) method can improve student learning outcomes. This can be seen by changes in learning outcomes in each cycle from cycle I to cycle III.